STUDY OF ONE AT GRADE HIGHWAY-RAIL INTERSECTION - (NIM 25001069), SAID
At grade intersection is a place that potentially become a source of significant traffic delay. This Thsis studies the traffic characteristics and delay occurred in one at grade highway-rail intersection. At grade highway-rail intersection studied was an intersection between Jl. Laswi and railway, and Tar-tic ticm studied was the traffic from Jl. Gatot Subroto to Jl. R.E. Martadinata. J1. Laswi was 4/2 :) with lane width of 4 x 3.5 m, median width of 1.8 m and shoulder width of 2 x 3.0 m. The -aiiwa) was a double track, which equipped with safety gates. The distance between safety gates at the at grade highway-rail intersection was 17.0 m. Data taken on Thursday, April 22, 2004, manual traffic counting was carried out at 05.00 a.m. and ended at 21.00 p.m. Traffic data were collected by using two video cameras and it was carried out in two periods, i.e. at 07.45 am until 09.45 a.m. and 12.45 p.m. until 13.45 p.m. The locations of the survey of traffic were 2 locations, one location was at 410 m before the gate and another one was at ,u m after the gate. There were 70 trains passing the intersection per day. The trains could be classified into four groups e inspection-train, container train, economy train, and executive train. From the research, the capacity of inner lane for before and after at grade highway-rail intersection were 1,396.51 pcu/hr., and 1.413.83 pcu/hr., respectively. At the outer lane, capacity value before and after at grade intersection were 1,911.32 pcu/hr. and 1,154.02 pcu/hr., respectively. The traffic volume during 16 hours was 102,450 vehicles with direction distribution about 50/50. Within 3 hours observation, for inner lane, the proportion of the traffic observed before at-grade highway-rail intersection, percentage of heavy vehicle, light vehicle, and motorcycle were as follow 48 °; 58.58%; and 37.94%, and that after at grade intersection were as follow 1.31%; 25.43% and '3.26%. The traffic proportion of the outer lane, observed location before at grade highway-rail intersection were as follow 4.23%; 49.81%; and 45.96%, and that after at grade highway-rail intersection were as follow 2.08%; 34.56% and 63.36%. Linear regression was used in analysis the relationship between speed and density. The results were as follow, for inner lane at before at grade highway-rail intersection was Ussbl = - 0.9547D 73.012; after at grade intersection was Ussti = - 0.1587D 29.958. For outer lane at before at grade highway-rail intersection equation was Ussbl = - 0.3835D 54.152; and that after at grade intersection was Ussti = - 0.2286D 32.483. Predicted delays obtained from the researched consist of delay caused by closing gate and geometric delay due to the existence of the railway. Total traffic delay per day calculated for two lanes about 15,725.45 pcu.hr., which consisted bf delay caused closing gate about 13,350.41 pcu.hr. and delay caused opening gate about 2,375.04 pcu.hr.